Argumentation, Adversariality, and Social Norms. (29th September 2020) - Yap, Audrey
Abstract: Janice Moulton's "The Adversary Method: A Philosophical Paradigm" articulated several criticisms of the popular idea of philosophy as adversarial debate. Moulton criticizes it on epistemic grounds, arguing that philosophy's overreliance on adversarial debate is to the detriment of its goals. Some, notably Trudy Govier, have argued in favor of at least a minimal adversariality, governed by norms of respectful argumentation. This paper suggests that Govier's faith in these norms is misplaced, because it neglects the social circumstances of the arguers. While some authors have argued that politeness and aggression apply differently to those of different genders, this paper extends that analysis to social identities other than gender. In fact, given certain assumptions about the philosophy of language, engagement in polite adversarial debate may not even be possible for people occupying certain social locations.